Estimation of heritability, breeding values and genetic trends for growth traits of exotic goat - Hassan, MR; Sultana, S; Iqbal, A; Talukder, MAI (International Journal of Natural Sciences, 2016)
The present study was considered to estimate the variance components, heritability and prediction of breeding values (PBV) for important growth traits of exotic goat. Traits were considered birth weight, weaning weight, 6 months weight and weight at 9 months. Data were collected from the goat farm of Bangladesh livestock research institute (BLRI), Savar, Dhaka. Heritability values for the studied traits were estimated by Multivariate animal model using principles of Restricted Maximum Likelihood (REML) procedure. The mean birth weight, weaning weight, 6 and 9 months weight of exotic goat were recorded as 1.41, 7.39, 11.06 and 14.09 kgs respectively. Calculated Heritability values were 0.33, 0.39, 0.45 and 0.32 for the birth weight, weaning weight, and weight at 6 and 9 month respectively. Heritability estimates for different growth traits of exotic goat were found higher but the highest for the 6 month body weight (0.45). Among the live weight categories of exotic goat the maximum average PBV was found for the 6-month body weight (7.42). The genetic trends among the generations in birth and 6 month weight were increased from foundation to generation 1 and 2. Therefore, the results revealed that the 6 months body weight can be considered as an indicator of growth and sire selection and could be effective for enhancing growth of exotic kids. International Journal of Natural Sciences (2013), 3(1-4) 7-11